EMIGMA OF MAIRONIS - Razauskas, Dainius (Literatūra, 2013)
One strophe of the Lithuanian poetry patriarch Maironis is analysed in the article. Firstly, attention is drawn to some Lithuanian mythological notions used in the strophe, namely of the Sun as a personified heavenly queen, of the dawn as woven fabric, of the gold as a traditional attribute of the sun and dawn etc. Secondly, notice is taken of the formal features of the strophe (alliteration), one line of which, describing the sun as “wraped oneself into red veil woven with gold” (apsisupusi šydu, auksu austu, raudonu), almost precisely coinsides with the traditional riddle “warped blue, woven red, strewn with gold” (mėlynai austa, raudonai atausta, auksu išbarstyta). Furthermore, the solution of the riddle is aušra (“dawn”), and the title of the Maironis’ verse is Saulei tekant (“Rising of the sun”), i.e. “Dawning”. Thus, Maironis has in the verse presented a riddle and, taking into account this revelation of his previously unnoticed particulary close relation with the traditional lore, himself still remains a riddle.